STUDI KARAKTERISTIK MASYARAKAT DI DAERAH ALIRAN SUNGAI BATANG MAHAT KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTA - Rahmi, Fahdila; Erita, Yeni; U, Iswandi (STKIP PGRI Sumbar, 2013)
The purpose of this research was to gother and describe the data and information about (1) The profession of society around Batang Mahat river Kecamatan Pangkalan Koto Baru Kabupaten Lima Puluh Kota (2) The use of area around Batang Mahat river Kecamatan Pangkalan Koto Baru Kabupaten Lima Puluh Kota (3) Educational level of society around Batang Mahat Kecamatan Pangkalan Koto Baru Kabupaten Lima Puluh Kota.Methodology of this research was descriptive research. More over, population of this research was society around Batang Mahat river. The total of population was 1060 KK. Then, the sampling technique of each area used purposive sampling. Furthermore, it was pointed that JorongÂ Becah Lumpur represented the area of Batang Mahat river in upper watershed, Jorong Batu Balah represented the area of Batang Mahat river in middle watershed, and Jorong Koto Lamo represented the area of Batang Mahat river in lower watershed, by using proportional random sampling technique. The respondent was determined randomly based on the proportion of each Jorong about 15% for each area sampling. Therefore, the total of respondents in this research was 109.The finding of this research showed that the profession of society in the area of Batang Mahat river Kecamatan Pangkalan Koto Baru Kabupaten Lima Puluh Kotawas 91 inhabitants as farmers (83.49%), the use of area that was generally for plantation of Gambier was 85 inhabitants (78.70%), education level of the society who were gradated in elementary was about 85 inhabitans (53.21%).